Improvements to the formation of lists of drugs for medical use: analysis of changes in the Government Decree no. 871 - V. V. Omelyanovskiy; E. A. Maksimkina; O. I. Ivakhnenko; M. V. Avxentyeva; M. V. Sura; G. R. Khachatryan (IRBIS LLC, 2020)
The article presents a description of amendments of the Russian Federation Government Decree No. 871 from August 28, 2014 (with amendments from November 20, 2018). The authors analyzed the historical development of approaches for complex drug assessment in Russia, also criteria for its evaluation were under investigation. The changes affecting both the order and the procedure of forming the lists of medical drugs for medical use are reviewed. The particularities of the current procedure for the formation of lists of drugs for medical use are described in detail. In reliance on the analysis, further direction for improvement/development of the system of formation the lists of medical drugs for medical use are educed (List of Vital and Essential Medicines, List of Medical Drugs for Certain Categories of Citizens, List of High-Cost Medical Drugs).